Pengelolaan Tenaga Pendidik dan Kependidikan dalam Meningkatkan Mutu Peserta Didik - Nasution, Riski Humairoh; Paizah, Nurul; Safitri, Rini (MATAAZIR: Jurnal Administrasi dan Manajemen Pendidikan, 2025)
This study aims to examine the management of teaching and educational staff in improving student quality. Using a descriptive qualitative approach, data were collected through interviews, observations, and document analysis in several schools. The findings indicate that the management of educational personnel directly affects students’ academic and character development. However, challenges such as lack of training, improper placement, and weak evaluation systems remain significant obstacles. This study recommends the need for strategic planning and ongoing professional development to ensure that educational human resource management effectively supports high-quality learning processes.Keywords: Teaching and Educational Personnel, Student Quality, Management